2019
DOI: 10.1108/ijaim-10-2017-0118
|View full text |Cite
|
Sign up to set email alerts
|

Is corporate governance relevant to the quality of corporate social responsibility disclosure in large European companies?

Abstract: Purpose This paper aims to report on the quality of corporate social responsibility (CSR) disclosure in S&P Europe 350 companies. The paper also examines the impact of corporate governance structure and other firm-specific characteristics on the quality of CSR disclosure in European companies. Design/methodology/approach The paper uses a disclosure index adopted from Jizi et al. (2014). Moreover, the paper contributes to the CSR disclosure literature by developing a new index that includes all the aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
115
2
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(134 citation statements)
references
References 61 publications
11
115
2
6
Order By: Relevance
“…With the growing importance of CSR, recent studies proposed that independent directors may also align the interests of firms with those of stakeholders (Gallego-Álvarez & Pucheta-Martínez, 2020), and tested this proposition by incorporating board independence in CSR studies. However, the findings are inconclusive; some studies found that board independence improves CSR engagement (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020), others found that it decreases (Adel, Hussain, Mohamed, & Basuony, 2019), and still others found a neutral effect (Michelon & Parbonetti, 2012). Therefore, our study provides additional evidence of the influence of independent directors on CSRP.…”
Section: Findings and Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…With the growing importance of CSR, recent studies proposed that independent directors may also align the interests of firms with those of stakeholders (Gallego-Álvarez & Pucheta-Martínez, 2020), and tested this proposition by incorporating board independence in CSR studies. However, the findings are inconclusive; some studies found that board independence improves CSR engagement (Arayssi et al, 2019;Gallego-Álvarez & Pucheta-Martínez, 2020), others found that it decreases (Adel, Hussain, Mohamed, & Basuony, 2019), and still others found a neutral effect (Michelon & Parbonetti, 2012). Therefore, our study provides additional evidence of the influence of independent directors on CSRP.…”
Section: Findings and Discussionmentioning
confidence: 57%
“…Moreover, the findings of prior studies regarding the association between CSR committees and CSRP or reporting largely proved the existence of a positive relationship between the two variables, regardless of context, although there are some exceptions. While some European studies found a positive association between CSR committee and CSRP (Adel et al, 2019;García Martín & Herrero, 2020), another study sampling European and US firms found only a weak association between CSR committee and the social dimension of CSR disclosure, but not other dimensions;…”
Section: Findings and Discussionmentioning
confidence: 95%
“…However, no CSO study has been conducted yet. Most found a positive impact from CSR committees on CSR reporting, using cross-country samples (Adel et al 2019;Amran et al 2014; Gallego-Alvarez and Pucheta-Martinez 2020; Kend 2015; Michelon 2011; Pucheta-Martinez and Gallego-Alvarez 2019) and different countries: Italy (Cucari et al 2018;Rossi and Tarquinio 2017); the US (Hussain et al 2018); Pakistan (Mahmood et al 2018); and Spain (Fuente et al 2017). Moreover, CSR committee expertise (Rossi and Tarquinio 2017) and CSR committee duration (Garcia-Torea et al 2016) were related positively to CSR reporting.…”
Section: Csr Committees' Impact On Csr Reportingmentioning
confidence: 99%
“…In the academic literature, the study of CSR or sustainability committees has been closely linked to their relationship with corporate governance, especially its role in the board of directors and its interaction with other types of variables (diversity and independence of the board of directors). Therefore, in most cases, research has focused on CSR committees as a corporate governance variable for larger models [1,[9][10][11][12][13], mainly related to the disclosure of CSR or ESG information [1,[14][15][16][17][18][19]. In this regard, CSR committees have shown an influence on the volume and quality of CSR information issued by the company, showing its ability to act and decide on sustainability reporting.…”
Section: Introductionmentioning
confidence: 99%